Development of a Web-Based eChecklist System for Final Product Inspection in a Coachbuilding Company - Fatahillah, Gehan Gibran; Fansyah, Egi Al; Asyam, Muhammad Rizq Dzaki; Alsyah, Dwi Fahira; Nusantara, Abdul Hakim Satria; Saleh, Rayhan Zahwan (Electronic Integrated Computer Algorithm Journal, 2026)
This final project develops a web-based eChecklist system to support the final product inspection process in a coachbuilding company. The system is designed to replace manual checklist recording, which is often inefficient, prone to human error, difficult to track, and lacks real-time accessibility. The objective of this project is to improve the consistency and accuracy of inspection records, streamline communication among inspectors, supervisors, and administrators, and provide reliable documentation for each inspected unit. The system was developed using PHP with the Laravel framework and implemented using the Rapid Application Development (RAD) method. The main features include user authentication, role-based access control, digital checklist input, checklist validation, inspection history tracking, and report export. Testing was conducted on core functionalities such as login, role-based access, checklist submission, validation, status tracking, user and role management, and report generation. The results show that all tested functionalities worked properly and achieved the expected outcomes. It can be concluded that the web-based eChecklist system is able to support final inspection activities more effectively, improve data traceability, and enhance operational reliability in the coachbuilding quality control process.